Light-cone sum rules analysis of $$Ξ _{QQ^{′ }q}→ Λ _{Q^{′ }}$$ ΞQQ′q→ΛQ′ weak decays - Yu-Ji Shi; Ye Xing; Zhen-Xing Zhao (European Physical Journal C: Particles and Fields, 2019)
Abstract We analyze the weak decay of doubly-heavy baryon decays into anti-triplets $$Λ _Q$$ ΛQ with light-cone sum rules. To calculate the decay form factors, both bottom and charmed anti-triplets $$Λ _b$$ Λb and $$Λ _c$$ Λc are described by the same set of leading twist light-cone distribution amplitudes. With the obtained form factors, we perform a phenomenology study on the corresponding semi-leptonic decays. The decay widths are calculated and the branching ratios given in this work are expected to be tested by future experimental data, which will help us to understand the underlying dynamics in doubly-heavy baryon decays.